Frentes culturales: para una comprensión dialógica de las culturas contemporáneas - Jorge A. González (Estudios sobre las Culturas Contemporáneas)
This text presents the perspective of Cultural Fronts for the study of the cultural dynamics of complex societies. More than a new concept, this perspective provides a different manner of interrogating and understanding the complex significative dimension of everyday life. The author develops the idea that by means of the perspective Cultural Fronts, that which we consider and live as normal, self-evident, truthful and obvious in wliatever place or time, must be imderstood as a momentaiy state of a collective and provisional symbohc order. The study of the symbolic dimension of hfe from the perspective of cultural fronts allows us to know how our most prized and shared representations and our most loved sentiments have been created, and at the same time, opens us up to the possibility of understanding the development and construction of diverse modes and strategies of symbohc convergence and integration. For this purpose, this paper has two large sections. The first exphcates the theoretical bases of the approach and the second develops the four perspectives that converge in the methodological perspective of cultural fronts. Finally, we will see that this approach can contribute, through its own process of inquiry, materials and perspectives for woricing on horizontal networks and on processes of social empowerment.